KAPASITAS APARATUR SIPIL NEGARA TERHADAP EFEKTIVITAS PELAYANAN PUBLIK PADA BIDANG PENCATATAN SIPIL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SUNGAI PENUH: Hengki Pernanda - Pernanda, Hengki (Qawwam : The Leader's Writing, 2020)
Service is a very important task that must be found from the figure of the government apparatus as a servant of the community, namely that the community must carry out its duties that always serve the interests of the community and meet every need of the community in accordance with applicable regulations. Serving and protecting the community is the main function of every government apparatus in carrying out government duties. The services provided by the government apparatus to the community must be in accordance with their authority. The reality that occurs until now there are still complaints from the community such as the unknown requirements, convoluted and also uncertainty in the administration of administration and the attitude of government officials who are less responsive to what is the needs of each community. In carrying out public services there is a tendency for injustice to exist in public services where people classified as poor will find it difficult to obtain services. To find out howcapacity of the state civil apparatus on the effectiveness of public services in the Dinas Kependudukan dan Pencatatan Sipil Kota Sungai Penuh. The approach used in this study is a qualitative study, because it determines and reports the existing situation according to its reality and by measuring it. Typical qualitative research to find out attitudes, opinions, opinions, information, domography, circumstances and procedures. The informants in this study were 8 people. This study uses data collection techniques namely field research, library research, and interviews. From the interviews conducted by the researchers concluded that the services carried out by the Sungai Penuh village office staff were done well and in accordance with public service procedures.